Gender Inequality in Workplace (Study Case: Indonesia) - Noviyanti Soleman (AL-WARDAH: Jurnal Kajian Perempuan, Gender dan Agama, 2019)
In Indonesia, gender issue has been develop since long time ago and set under the law of Indonesia. The President Instruction No 9 of 2000 about gender mainstreaming to decrease the gap between men and women in accessing the development, improve the participation and understanding towards development. However, the effort of gender equality in Indonesia has to face many obstacles. According to World Economic Forum, among 149 countries Indonesia placed in the rank of 85 regarding to the gender gap issue of 2018 such as in economic participation and opportunity which means not in the good condition. The paper aims to explore the phenomena of gender inequality in workplace in Indonesia. To answer the research question, the author use qualitative research method with secondary data and analyze through thematic analysis approach. The author also use the theory of structural functionalism by Parsons and Bales (1955) to analyze the data. The result shows that the gender inequality impacted to division of labor such